Nanometer RuAg / heterojunction MoO3 / TiO2 composite catalyst as well as preparation method and application thereof
Through the micropore-mesoporous gradient structure of nano-RuAg/heterojunction MoO3/TiO2 composite catalyst and the synergistic effect of heterojunction MoO3/TiO2 and RuAg nanoalloy, the efficiency of existing adsorbents in low-concentration VOCs gas treatment is solved. The complex problems of low and desorption achieve catalytic degradation after adsorption and improve the treatment effect of VOCs.
Patent Information
- Application Number
- CN202411092458.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-01-07
AI Technical Summary
When existing adsorbents treat low-concentration VOCs gases, their adsorption efficiency is low and the desorption process is complex, making it difficult to achieve efficient capture and degradation.
Using nano-RuAg/heterojunction MoO3/TiO2 composite catalyst, the catalyst has a micropore-mesoporous gradient pore structure, combining adsorption and catalytic functions, the synergistic effect of heterojunction MoO3/TiO2 and RuAg nano alloy is realized post-adsorption catalysis. degradation.
It improves the adsorption efficiency and processing effect of VOCs, simplifies the process flow, and enhances the visible photocatalytic degradation performance of VOCs.
Smart Images

Figure CN119259043A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental treatment, and in particular relates to a nano RuAg / heterojunction MoO3 / TiO2 composite catalyst and a preparation method and application thereof. Background Art
[0002] Efficient treatment technologies for volatile organic compounds (VOCs) have received extensive attention. They are mainly divided into two methods: capture (condensation, absorption, adsorption, membrane separation, etc.) and destruction (thermal incineration, thermal catalysis, plasma, photocatalysis, etc.). The destruction technology requires first capturing and enriching low-concentration VOCs gases in the air. Adsorption is currently the most widely used VOCs capture technology, with high maturity, simple operation process and relatively low economic cost. The technical core of the adsorption method lies in the development of high-performance adsorbents with high VOCs adsorption capacity, controllable desorption and easy regeneration. At present, the adsorbents used for VOCs gas capture are mainly porous materials, such as activated carbon, activated carbon fiber, diatomaceous earth, mesoporous silica, metal organic frameworks (MOFs) and molecular sieves. Activated carbon and activated carbon fiber are carbon-based porous materials with large adsorption capacity, acid and alkali resistance and low cost. However, their abundant surface groups are easy to chemically adsorb or form stable hydrogen bonds with VOCs molecules, and desorption / desorption is not complete. In addition, carbon-based materials are not resistant to high temperatures, resulting in difficulty in regeneration. Diatomaceous earth has poor hydrothermal stability and is mainly a macroporous structure, which is not conducive to the adsorption of VOCs gases at low concentrations. Mesoporous silica is limited by its own large mesopores, and its adsorption and binding force for VOCs molecules with smaller kinetic diameters is relatively weak, and its ability to enrich low-concentration VOCs gases is poor. Metal organic framework compounds have a high adsorption capacity for VOCs molecules, but their precursor preparation cost is high. It is still in the basic research and development stage; molecular sieves are highly ordered in molecular size, have microporous channels with adjustable pore size, rich skeleton structure, and good thermal stability. They have been widely used in industrial adsorption / separation processes, among which molecular sieve rotor technology has been successfully applied to the adsorption and capture of VOCs gases emitted by industry. Molecular sieve adsorption rotors usually use honeycomb base profiles rolled up with inorganic fiber paper, and hydrophobic molecular sieves are coated / grown on the channel surface of the honeycomb porous structure, and finally sintered to form an integral molecular sieve adsorption rotor. However, its treatment of VOCs is mainly adsorption, and it is easy to adsorb saturated, resulting in reduced adsorption efficiency, desorption after adsorption, oxidation and other process flows are relatively complicated. Summary of the invention
[0003] In view of this, in order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a nano RuAg / heterojunction MoO3 / TiO2 composite catalyst and its preparation method and application. The catalyst has a microporous-mesoporous gradient pore structure, has both adsorption and catalytic effects, first adsorbs and then catalytically degrades, improves the adsorption efficiency and treatment effect of VOCs, and simplifies the VOCs treatment process.
[0004] The first aspect of the present invention provides a nano RuAg / heterojunction MoO3 / TiO2 composite catalyst, which has a microporous-mesoporous gradient pore structure. The nano RuAg / heterojunction MoO3 / TiO2 composite catalyst is composed of mesoporous TiO2 composited with microporous MoO3 to form heterojunction MoO3 / TiO2 and then composited with RuAg nano alloy.
[0005] The second aspect of the present invention provides a method for preparing the above-mentioned nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst, comprising the following steps:
[0006] S1. Mesoporous nano-TiO2 is added to a tetrahydrate ammonium molybdate solution with a pH of 1-2, and after a hydrothermal reaction, the precipitate is washed, dried, and calcined to obtain a heterojunction MoO3 / TiO2;
[0007] S2. Add heterojunction MoO3 / TiO2 into deionized water, disperse it evenly with ultrasound, add RuCl3 solution and AgNO3 solution, adjust the pH value to 10.8, then drop KBH4 solution into it to obtain a reaction solution, stir the reaction solution to react, filter out the filtrate after the reaction is completed to obtain a product, wash the product with deionized water until there is no chloride ion and sulfate ion in the filtrate, and dry it in vacuum to obtain a nano RuAg / heterojunction MoO3 / TiO2 composite catalyst.
[0008] Furthermore, in step S1, the preparation method of the ammonium molybdate tetrahydrate solution with a pH of 1.0 is as follows: solid ammonium molybdate tetrahydrate is dissolved in deionized water, magnetically stirred until the solid is completely dissolved, and then 4 mol / L nitric acid solution is slowly added dropwise to adjust the pH to 1.0.
[0009] Furthermore, in step S2, the pH value is adjusted to 10.8, specifically, the pH value is adjusted using ammonia water with a concentration of 1-2 mol / L.
[0010] Furthermore, the preparation method of the mesoporous nano-TiO2 is as follows: dissolve butyl titanate in anhydrous ethanol, add nano-C, add a mixture of anhydrous ethanol, glacial acetic acid and deionized water dropwise while stirring, continue stirring after hydrolysis to form a sol, let stand for 2-3 days after gel is formed, vacuum dry at 70-90°C for 8-10h to obtain a powder, grind it and air-roast it at 450-550°C in a muffle furnace for 2-4 hours to obtain mesoporous nano-TiO2.
[0011] Furthermore, the molar ratio of butyl titanate, anhydrous ethanol, glacial acetic acid, deionized water and nano-C is 1:(20-40):(1-2.5):(2-6):2.
[0012] Furthermore, in step S1, the mass ratio of ammonium molybdate tetrahydrate to mesoporous nano-TiO2 in the ammonium molybdate tetrahydrate solution is 1:(2.4-3.3).
[0013] Furthermore, in step S1, the mass ratio of ammonium molybdate tetrahydrate to mesoporous nano-TiO2 in the ammonium molybdate tetrahydrate solution is 1:(2.4-3.3).
[0014] Furthermore, in step S1, the mass ratio of ammonium molybdate tetrahydrate to mesoporous nano-TiO2 in the ammonium molybdate tetrahydrate solution is (2.45-3.26).
[0015] Furthermore, in the heterojunction MoO3 / TiO2, the mass ratio of MoO3 to TiO2 is 1:(3-4).
[0016] Furthermore, in step S1, the temperature of the hydrothermal reaction is 160° C. and the time is 5 hours.
[0017] Furthermore, in step S1, the calcination is performed at 350° C. for 2-3 hours.
[0018] Furthermore, in step S2, in the reaction solution, the molar ratio of RuCl3 and AgNO3 is 7:3, 1:1 or 3:7; the mass ratio of RuAg alloy to heterojunction MoO3 / TiO2 is 1:(99-19); and the amount of KBH4 added is 5 times the sum of the molar numbers of RuCl3 and AgNO3.
[0019] Furthermore, in step S2, the stirring reaction time is 2-6 hours.
[0020] The third aspect of the present invention provides the use of the above-mentioned nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst or the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst prepared by the above-mentioned preparation method in removing VOCs.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1) The nano-TiO2 with a mesoporous structure and the MoO3 with a microporous structure in the RuAg / heterojunction MoO3 / TiO2 composite catalyst form a heterojunction with a microporous-mesoporous gradient pore structure, which has a large specific surface area, short pores, and good VOCs adsorption performance, thereby improving the adsorption efficiency of the composite catalyst for VOCs.
[0023] 2) The band gap energy of TiO2 is about 3.2eV, and the band gap energy of MoO3 is about 2.8eV. The band gap of TiO2 can be induced to be reduced, so that the light absorption of the composite material can be extended to a longer wavelength to obtain higher visible light catalytic activity. TiO2 is a typical n-type semiconductor, while MoO3 belongs to a p-type semiconductor and the conduction band and valence band positions are higher than TiO2. The construction of p-MoO3 / n-TiO2 heterojunction can improve the charge transfer process by hindering charge recombination and producing more active oxygen free radicals and ·OH, thereby improving the catalytic performance. In addition, RuAg alloy has good conductivity and can well change the d band position and catalyst electronic structure of the MoO3 / TiO2 heterojunction, change the electron cloud density on the surface of the composite catalyst, and timely transfer the electrons on the catalyst surface, so that the electron-hole separation efficiency is improved and more ·OH is produced. The synergistic effect makes the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst have a high visible light catalytic degradation performance for VOCs.
[0024] 3) The adsorption and catalysis are integrated. The MoO3 micropores in the catalyst adsorb and enrich VOCs. Since TiO2 has a mesoporous structure, the gradient between the microporous MoO3 and the mesoporous TiO2 allows the enriched VOCs adsorbed by the MoO3 micropores to be quickly transferred to the TiO2 surface and catalytically degraded by the RuAg / heterojunction MoO3 / TiO2 composite catalyst. The catalyst has both adsorption and catalytic effects, first adsorbing and then catalytically degrading, improving the adsorption efficiency and treatment effect of VOCs and simplifying the VOCs treatment process. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.
[0026] Figure 1 Schematic diagram of VOCs removal by nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst under visible light excitation;
[0027] Figure 2 The XRD spectrum of the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst of Example 1;
[0028] Figure 3A -E is the XPS graph of the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst of Example 1;
[0029] Figure 4 These are the test results of the adsorption capacity of the commercially available zeolite molecular sieve ZSM-5 and the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst of Example 1. DETAILED DESCRIPTION
[0030] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0031] All raw materials of the present invention are not particularly limited in their sources and can be purchased from the market or prepared according to conventional methods well known to those skilled in the art.
[0032] The present invention will be described in detail below through examples.
[0033] Unless otherwise specified, all materials used are common commercially available products.
[0034] Example 1
[0035] (1) Synthesis of mesoporous nano-TiO2: 17 mL of butyl titanate was dissolved in 22 mL of anhydrous ethanol, 1.2 g of nano-C was added, and a mixture of 22 mL of anhydrous ethanol, 3.6 mL of glacial acetic acid and 3.6 mL of deionized water was added dropwise with stirring. After hydrolysis to form a sol, stirring was continued. After the gel was formed, it was allowed to stand for 2-3 days. After vacuum drying at 80°C for 8-10 hours, the obtained powder was ground and calcined in a muffle furnace at 500°C for 3 hours to obtain 4 g of mesoporous nano-TiO2.
[0036] (2) Synthesis of heterojunction MoO3 / TiO2: At room temperature, weigh 1.226 g of ammonium molybdate tetrahydrate solid ((NH4)6Mo7O 24·4H2O) was dissolved in 75mL deionized water, and magnetic stirring was performed for 30min until the solid was completely dissolved. Then, 4mol / L nitric acid solution was slowly added dropwise, the pH was adjusted to 1.0, and 3g of the mesoporous hollow nano-TiO2 obtained in step (1) was added. After being fully stirred, a white suspended precursor solution was obtained. The solution was poured into a 100mL high-pressure reactor containing a polytetrafluoroethylene liner, sealed and placed in a constant temperature blast drying oven, and hydrothermally reacted at 160°C for 5h. After the hydrothermal reaction was completed, the supernatant was poured out, and the white precipitate in the reactor liner was poured into a centrifuge tube. After the precipitate was washed alternately with deionized water and anhydrous ethanol for 3 times, the precipitate was placed in a constant temperature blast drying oven at 80°C for drying, and the obtained powder was roasted at 350°C to obtain a heterojunction MoO3 / TiO2 with a mass ratio of MoO3 to TiO2 of 1:3.
[0037] (3) Synthesis of nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst: 1 g of heterojunction MoO3 / TiO2 synthesized in step (2) was added to 50 mL of deionized water and dispersed evenly by ultrasonication to form a MoO3 / TiO2 dispersion. 1.48 mL of 0.1 mol / L RuCl3 solution and 1.48 mL of 0.1 mol / L AgNO3 solution were added. The pH value of the dispersion was adjusted to 10.8 with aqueous ammonia under stirring. 7.4 mL of concentrated The catalyst is prepared by adding a KBH4 solution with a concentration of 0.2 mol / L, stirring for reaction for 2-6 hours, filtering after the reaction is completed, washing with deionized water until there is no chloride ion and sulfate ion in the filtrate, and vacuum drying at 80-120° C. to obtain a nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst in which the molar ratio of RuAg is 1:1, the sum of the content of RuAg nano alloy is 3% of the total amount of nano-RuAg / heterojunction MoO3 / TiO2, and the mass ratio of MoO3 to TiO2 is 1:3.
[0038] Example 2
[0039] (1) Synthesis of mesoporous nano-TiO2: 17 mL of butyl titanate was dissolved in 22 mL of anhydrous ethanol, 1.2 g of nano-C was added, and a mixture of 22 mL of anhydrous ethanol, 3.6 mL of glacial acetic acid and 3.6 mL of deionized water was added dropwise with stirring. After hydrolysis to form a sol, stirring was continued. After the gel was formed, it was allowed to stand for 2-3 days. After vacuum drying at 80°C for 8-10 hours, the obtained powder was ground and calcined in a muffle furnace at 500°C for 3 hours to obtain 4 g of mesoporous nano-TiO2.
[0040] (2) Synthesis of heterojunction MoO3 / TiO2: At room temperature, weigh 1.226 g of ammonium molybdate tetrahydrate solid ((NH4)6Mo7O 24·4H2O) was dissolved in 75mL deionized water, magnetically stirred for 30min until the solid was completely dissolved, then 4mol / L nitric acid solution was slowly added dropwise, pH was adjusted to 1.0, 4g of mesoporous nano-TiO2 obtained in step (1) was added, and a white suspended precursor solution was obtained after sufficient stirring. The solution was poured into a 100mL high-pressure reactor containing a polytetrafluoroethylene liner, sealed and placed in a constant temperature blast drying oven, and hydrothermally reacted at 160°C for 5h. After the hydrothermal reaction was completed, the supernatant was poured out, and the white precipitate in the reactor liner was poured into a centrifuge tube. After the precipitate was washed alternately with deionized water and anhydrous ethanol for 3 times, the precipitate was placed in a constant temperature blast drying oven at 80°C for drying, and the obtained powder was roasted at 350°C to obtain a heterojunction MoO3 / TiO2 with a mass ratio of MoO3 to TiO2 of 1:4.
[0041] (3) Synthesis of nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst: 1 g of heterojunction MoO3 / TiO2 synthesized in step (2) was added to 50 mL of deionized water and dispersed evenly by ultrasonication to form a MoO3 / TiO2 dispersion. 3.57 mL of 0.1 mol / L RuCl3 solution and 1.53 mL of 0.1 mol / L AgNO3 solution were added. The pH value of the dispersion was adjusted to 10.8 with aqueous ammonia under stirring. 10.2 mL of concentrated The catalyst is prepared by adding a KBH4 solution with a concentration of 0.25 mol / L, stirring for reaction for 2-6 hours, filtering after the reaction is completed, washing with deionized water until there is no chloride ion and sulfate ion in the filtrate, and vacuum drying at 80-120° C. to obtain a nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst in which the molar ratio of RuAg is 7:3, the sum of the content of RuAg nano alloy is 5% of the total amount of nano-RuAg / heterojunction MoO3 / TiO2, and the mass ratio of MoO3 to TiO2 is 1:4.
[0042] Example 3
[0043] (1) Synthesis of mesoporous nano-TiO2: 17 mL of butyl titanate was dissolved in 22 mL of anhydrous ethanol, 1.2 g of nano-C was added, and a mixture of 22 mL of anhydrous ethanol, 3.6 mL of glacial acetic acid and 3.6 mL of deionized water was added dropwise with stirring. After hydrolysis to form a sol, stirring was continued. After the gel was formed, it was allowed to stand for 2-3 days. After vacuum drying at 80°C for 8-10 hours, the obtained powder was ground and calcined in a muffle furnace at 500°C for 3 hours to obtain 4 g of mesoporous nano-TiO2.
[0044] (2) Synthesis of heterojunction MoO3 / TiO2: At room temperature, weigh 1.226 g of ammonium molybdate tetrahydrate solid ((NH4)6Mo7O 24·4H2O) was dissolved in 75mL deionized water, magnetically stirred for 30min until the solid was completely dissolved, then 4mol / L nitric acid solution was slowly added dropwise, pH was adjusted to 1.0, 4g of mesoporous nano-TiO2 obtained in step (1) was added, and a white suspended precursor solution was obtained after sufficient stirring. The solution was poured into a 100mL high-pressure reactor containing a polytetrafluoroethylene liner, sealed and placed in a constant temperature blast drying oven, and hydrothermally reacted at 160°C for 5h. After the hydrothermal reaction was completed, the supernatant was poured out, and the white precipitate in the reactor liner was poured into a centrifuge tube. After the precipitate was washed alternately with deionized water and anhydrous ethanol for 3 times, the precipitate was placed in a constant temperature blast drying oven at 80°C for drying, and the obtained powder was roasted at 350°C to obtain a heterojunction MoO3 / TiO2 with a mass ratio of MoO3 to TiO2 of 1:4.
[0045] (3) Synthesis of nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst: 1 g of heterojunction MoO3 / TiO2 synthesized in step (2) was added to 50 mL of deionized water and dispersed evenly by ultrasonication to form a MoO3 / TiO2 dispersion. 0.29 mL of 0.1 mol / L RuCl3 solution and 0.67 mL of 0.1 mol / L AgNO3 solution were added. The pH value of the dispersion was adjusted to 10.8 with aqueous ammonia under stirring. 4.8 mL of concentrated The catalyst is prepared by adding a KBH4 solution with a concentration of 0.1 mol / L, stirring for reaction for 2-6 hours, filtering after the reaction is completed, washing with deionized water until there is no chloride ion and sulfate ion in the filtrate, and vacuum drying at 80-120° C. to obtain a nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst in which the molar ratio of RuAg is 3:7, the sum of the content of RuAg nano alloy is 1% of the total amount of nano-RuAg / heterojunction MoO3 / TiO2, and the mass ratio of MoO3 to TiO2 is 1:4.
[0046] Example 4
[0047] (1) Synthesis of mesoporous nano-TiO2: 17 mL of butyl titanate was dissolved in 22 mL of anhydrous ethanol, 1.2 g of nano-C was added, and a mixture of 22 mL of anhydrous ethanol, 3.6 mL of glacial acetic acid and 3.6 mL of deionized water was added dropwise with stirring. After hydrolysis to form a sol, stirring was continued. After the gel was formed, it was allowed to stand for 2-3 days. After vacuum drying at 80°C for 8-10 hours, the obtained powder was ground and calcined in a muffle furnace at 500°C for 3 hours to obtain 4 g of mesoporous nano-TiO2.
[0048] (2) Synthesis of heterojunction MoO3 / TiO2: At room temperature, weigh 1.226 g of ammonium molybdate tetrahydrate solid (NH4)6Mo7O 24·4H2O) was dissolved in 75mL deionized water, magnetically stirred for 30min until the solid was completely dissolved, then 4mol / L nitric acid solution was slowly added dropwise, pH was adjusted to 1.0, 4g of mesoporous nano-TiO2 obtained in step (1) was added, and a white suspended precursor solution was obtained after sufficient stirring. The solution was poured into a 100mL high-pressure reactor containing a polytetrafluoroethylene liner, sealed and placed in a constant temperature blast drying oven, and hydrothermally reacted at 160°C for 5h. After the hydrothermal reaction was completed, the supernatant was poured out, and the white precipitate in the reactor liner was poured into a centrifuge tube. After the precipitate was washed alternately with deionized water and anhydrous ethanol for 3 times, the precipitate was placed in a constant temperature blast drying oven at 80°C for drying, and the obtained powder was roasted at 350°C to obtain a heterojunction MoO3 / TiO2 with a mass ratio of MoO3 to TiO2 of 1:4.
[0049] (3) Synthesis of nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst: 1 g of heterojunction MoO3 / TiO2 synthesized in step (2) was added to 50 mL of deionized water and dispersed evenly by ultrasonication to form a MoO3 / TiO2 dispersion. 1.48 mL of 0.1 mol / L RuCl3 solution and 1.48 mL of 0.1 mol / L AgNO3 solution were added. The pH value of the dispersion was adjusted to 10.8 with aqueous ammonia under stirring. 7.4 mL of concentrated The catalyst is prepared by adding a KBH4 solution with a concentration of 0.2 mol / L, stirring for reaction for 2-6 hours, filtering after the reaction is completed, washing with deionized water until there is no chloride ion and sulfate ion in the filtrate, and vacuum drying at 80-120° C. to obtain a nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst in which the molar ratio of RuAg is 1:1, the sum of the content of RuAg nano alloy is 3% of the total amount of nano-RuAg / heterojunction MoO3 / TiO2, and the mass ratio of MoO3 to TiO2 is 1:4.
[0050] Table 1 shows the specific surface area, pore volume and pore size test results of the mesoporous nano-TiO2, heterojunction MoO3 / TiO2 and nano-RuAg / heterojunction MoO3 / TiO2 composite catalysts prepared in Example 1, Example 2, Example 3 and Example 4 measured by the N2 adsorption-desorption method.
[0051] As can be seen from Table 1, TiO2, heterojunction MoO3 / TiO2, and nano-RuAg / heterojunction MoO3 / TiO2 composite catalysts all have a large specific surface area. TiO2, heterojunction MoO3 / TiO2, and nano-RuAg / heterojunction MoO3 / TiO2 composite catalysts have a mesoporous structure and a large pore volume. The mesoporous TiO2 and the microporous MoO3 are combined to form a heterojunction MoO3 / TiO2 with a gradient pore structure, which is more conducive to the adsorption of VOCs.
[0052] Table 1
[0053]
[0054]
[0055] Figure 1 Schematic diagram of the removal of VOCs by nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst under visible light excitation. The band gap energy of TiO2 is about 3.2eV, and the band gap energy of MoO3 is about 2.8eV. The MoO3 / TiO2 heterojunction structure induces a reduction in the band gap of TiO2, so that the light absorption of the composite catalyst extends to a longer wavelength and obtains a higher visible light catalytic activity. TiO2 is a typical n-type semiconductor, while MoO3 belongs to a p-type semiconductor and the positions of the conduction band and valence band are higher than those of TiO2. The construction of p-MoO3 / n-TiO2 heterojunction can improve the catalytic performance by hindering charge recombination and improving the charge transfer process to produce more active oxygen free radicals and ·OH. In addition, RuAg alloy has good conductivity, which can better change the d band position of MoO3 / TiO2 heterojunction and the electronic structure of the catalyst, change the electron cloud density on the surface of the composite catalyst, and timely transfer electrons on the surface of the catalyst, so as to improve the efficiency of electron-hole separation and produce more. The synergistic effect makes the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst have a higher visible light catalytic degradation performance for VOCs, effectively degrading VOCs.
[0056] Figure 2 The XRD spectrum of the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst of Example 1. In the spectrum, 25.24°, 37.16°, 48.24°, 54.02°, 55.32° and 62.94° are characteristic diffraction peaks of anatase TiO2. The characteristic diffraction peaks at 12.82°, 23.38°, 25.72°, 27.38°, and 63.04° are characteristic diffraction peaks of orthorhombic phase α-MoO3, and 16.78° and 19.40° are characteristic diffraction peaks of hexagonal phase h-MoO3, indicating that microporous MoO3 and mesoporous TiO2 are well compounded to form a heterojunction structure of MoO3 / TiO2. The characteristic diffraction peaks of metal Ru and Ag are not seen in the figure, which may be because the particle size of Ru and Ag is too small to be detected.
[0057] FIG3 is an XPS graph of the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst of Example 1. As can be seen in FIG3, the Ag 3d spectrum ( Figure 3A ) There are many impurity peaks, but they can be divided into binding energies of 368.3 and 374.2 eV, indicating that Ag in the catalyst exists in pure Ag form.
[0058] Ru 3d spectrum( Figure 3B) indicates that the Ru in the catalyst is in the form of metallic Ru rather than oxide.
[0059] Figure 3C Ti 2p peaks at 458.3 and 464.1 eV can also be seen. The difference in binding energy between Ti 2p3 / 2 and Ti 2p1 / 2 is 5.8 eV. 4+ The existence of MoO3 / TiO2 in the form of RuAg alloy increases the binding energy of Ti 2p electrons, indicating that there is a strong interaction between MoO3 / TiO2 and RuAg alloy, which reduces the electron cloud density of Ti atoms.
[0060] XPS spectrum of O 1s ( Figure 3D ) The peak at 529.4 eV is the characteristic peak of Ti—O bond, and the peak at 532.0 eV is attributed to the characteristic peak of O atom in OH on the TiO2 surface.
[0061] XPS spectrum of Mo 3d ( Figure 3E ) can be confirmed that Mo exists in +6 valence, and no characteristic peaks of +4 or +5 valence Mo are found. XPS results further prove that Ru and Ag are deposited on the heterojunction MoO3 / TiO2 surface in the form of RuAg alloy nanoparticles rather than metal oxides, and the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst is successfully synthesized.
[0062] Test Case
[0063] The common VOCs toluene was used as a reference in a fixed bed reactor connected to a gas chromatograph. The gas chromatograph front detector was equipped with a hydrogen flame ionization detector and a thermal conductivity detector. During the test experiment, 100 mg of ZSM-5 and Example 1 nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst were placed in the reaction tubes respectively. Before the adsorption reaction, they were treated at 200°C for 12 hours to remove water and impurities in the catalyst. Toluene was heated and evaporated at a rate of 100 mL / min, and the concentration of toluene was measured to be 400 ppm. The saturated adsorption time and saturated adsorption capacity of toluene were measured. Adsorption capacity calculation formula:
[0064]
[0065] in:
[0066] F is the flow rate of toluene
[0067] C0 is the initial toluene concentration mg / m 3
[0068] C t is the concentration of toluene after t minutes, mg / m 3
[0069] t is the adsorption time
[0070] t s Saturation adsorption time
[0071] Figure 4 Table 2 and Table 3 are the adsorption capacity test results of the commercially available zeolite molecular sieve ZSM-5 and the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst of Example 1.
[0072] Table 2
[0073]
[0074] Figure 4 It can be seen that the adsorption time of ZSM-5 to reach adsorption saturation is 21 minutes, while the saturated adsorption time of the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst in Example 1 is 48 minutes, and after reaching adsorption saturation, the rate of increase of toluene concentration in the reaction tube after adsorption of the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst in Example 1 is much smaller than that of ZSM-5, which indicates that the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst in Example 1 has a good catalytic degradation effect on toluene.
[0075] As shown in Table 2, the adsorption capacity of ZSM-5 for toluene is 121.8 mg / g, and the adsorption capacity of the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst of Example 1 is 148.2 mg / g, which is 21.7% higher than that of ZSM-5.
[0076] Figure 4 The results in Table 2 show that the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst of Example 1 has a good treatment effect on VOCs.
[0077] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Although the embodiments of the present invention have been shown and described, it is understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the attached claims and their equivalents.
Claims
1. A nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst, characterized in that: The nano RuAg / heterojunction MoO3 / TiO2 composite catalyst has a microporous-mesoporous gradient pore structure. The nano RuAg / heterojunction MoO3 / TiO2 composite catalyst is formed by combining mesoporous TiO2 with microporous MoO3 to form heterojunction MoO3 / TiO2 and then combining it with RuAg nano alloy.
2. A method for preparing the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst according to claim 1, characterized in that: The preparation method comprises the following steps: S1. Mesoporous nano-TiO2 is added to a tetrahydrate ammonium molybdate solution with a pH of 1-2, and after a hydrothermal reaction, the precipitate is washed, dried, and calcined to obtain a heterojunction MoO3 / TiO2; S2. Add heterojunction MoO3 / TiO2 into deionized water, disperse it evenly with ultrasound, add RuCl3 solution and AgNO3 solution, adjust the pH value to 10.8, then drop KBH4 solution into it to obtain a reaction solution, stir the reaction solution to react, filter out the filtrate after the reaction is completed to obtain a product, wash the product with deionized water until there is no chloride ion and sulfate ion in the filtrate, and dry it in vacuum to obtain a nano RuAg / heterojunction MoO3 / TiO2 composite catalyst.
3. The preparation method according to claim 2, characterized in that: The preparation method of the mesoporous nano-TiO2 is as follows: dissolving butyl titanate in anhydrous ethanol, adding nano-C, dripping a mixture of anhydrous ethanol, glacial acetic acid and deionized water under stirring, hydrolyzing to form a sol and continuing to stir, standing for 2-3 days after forming a gel, vacuum drying at 70-90°C for 8-10h, grinding the obtained powder, and air-baking at 450-550°C in a muffle furnace for 2-4 hours to obtain the mesoporous nano-TiO2.
4. The preparation method according to claim 3, characterized in that: The molar ratio of butyl titanate, anhydrous ethanol, glacial acetic acid, deionized water and nano-C is 1:(20-40):(1-2.5):(2-6):
2.
5. The preparation method according to claim 2, characterized in that: In step S1, the mass ratio of ammonium molybdate tetrahydrate to mesoporous nano-TiO2 in the ammonium molybdate tetrahydrate solution is 1:(2.4-3.3).
6. The preparation method according to claim 2, characterized in that: In step S1, the temperature of the hydrothermal reaction is 160° C. and the time is 5 hours.
7. The preparation method according to claim 2, characterized in that: In step S1, the calcination is performed at 350° C. for 2-3 hours.
8. The preparation method according to claim 2, characterized in that: In step S2, in the reaction solution, the molar ratio of RuCl3 and AgNO3 is 7:3, 1:1 or 3:7; the mass ratio of RuAg alloy to heterojunction MoO3 / TiO2 is 1:(99-19); and the amount of KBH4 added is 5 times the sum of the molar numbers of RuCl3 and AgNO3.
9. The preparation method according to claim 2, characterized in that: In step S2, the stirring reaction time is 2-6 hours.
10. Use of the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst according to claim 1 or the nano-RuAg / heterojunction MoO3 / TiO2 composite catalyst prepared by the preparation method according to any one of claims 2 to 9 in removing VOCs.
Citation Information
Cited By
Nano modified formaldehyde-removing wall paint and preparation method thereof
CN120310351A
A nano-modified formaldehyde-free wall paint and preparation method thereof
CN120310351B